1995
DOI: 10.1007/bf03165040
|View full text |Cite
|
Sign up to set email alerts
|

Brain uptake and metabolism of [1-11C]octanoate in rats: Pharmacokinetic basis for its application as a radiopharmaceutical for studying brain fatty acid metabolism

Abstract: The uptake of octanoate in rat brain and its metabolism were investigated by means of intravenously injecting [1-11C] or [1-14C]octanoate as a tracer. The radioactivity in the cerebrum was increased by an injection of [1-11C]octanoate, and reached its peak level (0.33% ID/g) in about 2 to 5 min, and then decreased slowly. The cerebrum-to-blood ratio of the radioactivity increased with time over a period of 30 min. At 30 sec, [1-11C]octanoate that remained unchanged in the cerebrum accounted for only 8% of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 15 publications
1
29
0
Order By: Relevance
“…Measurements of radioactivity levels after infusion with both [1-11 C]-and [1-14 C] octanoate have shown that octanoate can readily cross the blood-brain barrier. 8 Further studies have shown that with infusion of [1-14 C]-or [1- 13 C] octanoate at 15% to 25% of caloric requirements, the labeled carbon appears predominantly in glutamine as compared with glutamate. As glutamine is predominantly found in astrocytes, this suggests that medium-chain fatty acids are primarily metabolized by astrocytes.…”
Section: Introductionmentioning
confidence: 99%
“…Measurements of radioactivity levels after infusion with both [1-11 C]-and [1-14 C] octanoate have shown that octanoate can readily cross the blood-brain barrier. 8 Further studies have shown that with infusion of [1-14 C]-or [1- 13 C] octanoate at 15% to 25% of caloric requirements, the labeled carbon appears predominantly in glutamine as compared with glutamate. As glutamine is predominantly found in astrocytes, this suggests that medium-chain fatty acids are primarily metabolized by astrocytes.…”
Section: Introductionmentioning
confidence: 99%
“…24,25 We have developed a fullyautomated apparatus for the preparation of the [1-11 C]carboxylic acids and used it for routinely supplying [1-11 C]octanoic acid to PET studies. 26 In the manipulation of radioactivity, it is most important to minimize the operator's exposure to radiation.…”
Section: Introductionmentioning
confidence: 99%
“…It was conjectured that the selection of glucose, the predominant substrate for brain energy metabolism, over fatty acids for energy metabolism in the brain may be evolutionarily beneficial to avoid the disadvantages of β-oxidation (Schonfeld and Reiser, 2013). While fatty acids are used by the brain as well (Ebert et al , 2003; Kuge et al , 1995; Panov et al , 2014), neurons have low level rate-setting fatty acid catabolism enzymes and are generally not thought to rely on fatty acid β-oxidation for bioenergetics (Cahoy et al , 2008; Lee and Wolfgang, 2012) (Schonfeld and Reiser, 2013). …”
Section: Brain Energy Metabolismmentioning
confidence: 99%